2018
DOI: 10.3946/kjme.2018.77
|View full text |Cite
|
Sign up to set email alerts
|

Impact of faculty development programs for positive behavioural changes among teachers: a case study

Abstract: PurposeFaculty development (FD) is essential to prepare faculty members to become effective teachers to meet the challenges in medical education. Despite the growth of FD programmes, most evaluations were often conducted using short questionnaires to assess participants’ satisfaction immediately after they attended a programme. Consequently, there were calls for more rigorous evaluations based on observed changes in participants’ behaviours. Hence, this study aims to explore how the FD workshops run by the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
0
19
0
6
Order By: Relevance
“…It is anticipated that the positive self-reported perceived confidence may motivate teachers and bring positive behavioral changes among them for teaching learning, educating the students, and assessing their performance. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that the positive self-reported perceived confidence may motivate teachers and bring positive behavioral changes among them for teaching learning, educating the students, and assessing their performance. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The rationale of the study was as follows: 1) participants’ reactions, perception, and self-confidence can usually be measured with retro–pre questionnaire immediately after the training program, and 2) it is believed that the positive self-reported perceived confidence may motivate teachers and bring positive behavioral changes among them for teaching learning, educating the students, and assessing their performance. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…However the years of professional experience varied and since repeated or continuous exposure or self -learning cannot be stopped, this is a common confounding factor in all such studies. Taking a student's feedback, whether they benefit, do faculty teach better, use more skills and perform better and ultimately how this benefits the society at large, is the future scope of this study and a recent study has shown that students want passionate teachers, willing to sacrifice and open to feedback (Lee et al, 2018). In this endeavour, the faculty development programs should be need based, flexible and global in their approach, their content should be related to relevant problems and specific objectives and they should develop from a teachers' training to a professional's development program (Bansal & Supe, 2007;Adkoli & Sood, 2009).…”
Section: Vol 13 No 1 2019mentioning
confidence: 99%
“…Some studies have explored learning, which included attitudinal changes and increases in knowledge or skills [9][10][11]. A few studies have assessed the changes in educational behavior of the participants in their multiple roles [12,13]. Most of these evaluations have also only had a focus on short term outcomes, especially at an individual level.…”
Section: Introductionmentioning
confidence: 99%